Design of photonic band gap aperture coupled fractal shape tri-band active antenna - Saeidi, Tale (2014)
Microwavefrequencies have a rangeof 300MHz to 300GHz, while according toFederal Communications commission (FCC) and Industrial, Scintific, Medical (ISM) band only some specific frequencies can be used for industrial applications;for instance 0.915 GHz, 1.8 GHz and 2.45 GHz were selected. Based on these three different frequencies, an antenna can be developed to resonate at these three frequencies with high performances like high gain and being applicable for the application related to this band (ISM). In this thesis, a new fractal shape has been used by mixing the Koch fractal shape and square loop to design more compact antenna resonating at three different frequencies. Then, a new Photonic Band Gap structure is exploited to either remove the undesired harmonic frequencies or pass the wanted harmonics. Besides, to suppress the surface current and fringing fields which cause the gain decrement some vias has been used. For integrating the amplifier as an active element to the antenna a matching circuit is needed, thus a n-section transmission line transformer (TLT) plays this role. After investigation of the four methods for finding the optimized value for each part of the TLT, the Genetic Algorithm (GA) showed themost advantageous result among the others. The maximum gain is delivered to the load (antenna) when a good matching between the amplifier and the antenna achieved. The antenna has the ability to resonate at three frequencies 0.915, 1.8 and 2.45 GHz, which can cover the ISM bandand its relating applications. Moreover, the antenna has a miniaturized size compared to the previous works by almost55% and the gain of the antenna for every each resonant frequency is 20.9, 19.85 and 20.88dBirespectively. Furthermore, there is a good agreement between the simulated and measuredresults approximately.